Cytoplasmic Relocalization of TAR DNA-Binding Protein 43 Is Not Sufficient to Reproduce Cellular Pathologies Associated with ALS In vitro - Wobst, Heike J.; Wesolowski, Steven S.; Chadchankar, Jayashree; Delsing, Louise; Jacobsen, Steven; Mukherjee, Jayanta; Deeb, Tarek Z.; Dunlop, John; Brandon, Nicholas J.; Moss, Stephen J. (Frontiers in Molecular Neuroscience, 2017)
Mutations in the gene TARDBP, which encodes TAR DNA-binding protein 43 (TDP-43), are a rare cause of familial forms of amyotrophic lateral sclerosis (ALS) and frontotemporal dementia (FTD). While the majority of mutations are found in the C-terminal glycine-rich domain, an alanine to valine amino acid change at position 90 (A90V) in the bipartite nuclear localization signal of TDP-43 has been described. This sequence variant has previously been shown to cause cytoplasmic mislocalization of TDP-43 and decreases protein solubility, leading to the formation of insoluble aggregates. Since the A90V mutation has been described both in patients as well as healthy controls, its pathogenic potential in ALS and FTD remains unclear. Here we compare properties of overexpressed A90V to the highly pathogenic M337V mutation. Though both mutations drive mislocalization of the protein to the cytoplasm to the same extent, M337V produces more significant damage in terms of protein solubility, levels of pathogenic phosphorylation, and formation of C-terminal truncated protein species. Furthermore, the M337V, but not the A90V mutant, leads to a downregulation of histone deacetylase 6 (HDAC6) and Ras GTPase-activating protein-binding protein (G3BP). We hypothesize that the A90V variant represents a genetic risk factor for ALS and FTD, that by itself is not sufficient to cause the full repertoire of deleterious phenotypes associated with TDP-43 proteinopathies, despite prominent cytoplasmic protein relocalization.